REFLECTION OF LEGAL CONSCIOUSNESS IN THE LEGAL SEMANTIC FIELD OF PROVERBS - Afshari , Afshan (Collection of scientific papers «ΛΌГOΣ», 2022)
Proverbs are part of the culture of every nation. They absorb the history of the nation, reflect and record all stages of its historical development, convey the spirit and energy, mentality, and attitude towards life of the people who speak a certain language. Proverbs is a living, moving organism that absorbs all the realities of the modern world, all the changes that occur in the life of society like a sponge, and reflects in many variants and transformations.